Energization of planetary pickup ions in the solar system. Issue 1 (28th January 2014) - Jarvinen, R.; Kallio, E.
<x xml:space="preserve">Abstract</x> We study the solar wind‐induced ion escape from planetary atmospheres at different radial heliospheric distances in the solar system. We derive histograms of the gyroaveraged E×B velocities, energies, and Larmor radii of planetary ions in the solar wind at Mercury, Venus, Earth, and Mars. The statistical analysis is based on the interplanetary Pioneer Venus Orbiter and OMNI solar wind data sets. In addition to the energization in the undisturbed solar wind we also model how planetary heavy ions get energized in the solar wind interaction of an unmagnetized planet at different distances to the Sun. We found that due to the Parker spiral, pickup ions are expected to be found on average at lower energies and at velocities more perpendicular to the solar wind flow, the closer to the Sun a planet or a comet is. According to a global hybrid simulation, planetary heavy ion energization is influenced qualitatively in a similar way in the presence of an induced magnetosphere than in the upstream solar wind under different Parker spiral angles due to fact that the structure of an induced magnetosphere depends strongly on the interplanetary magnetic field and solar wind conditions. Finally, the energization and dynamics of the pickup ions vary considerably with the solar activity. The variation is stronger the farther away from the Sun an object is. The Larmor radii of the pickup ions are largest during a solar minimum while the pickup ion energies are highest during the declining phase of a solar cycle.